Health care expenditure in the EU countries A panel data approach - Hysková, Ivana; Klosová, Anna, 1942-; Jackson, Ian; Vysoká škola ekonomická v Praze. Fakulta mezinárodních vztahů (2012)
This thesis examines the convergence in health care spending in euro area member countries during the period 1995-2010 and the influence of joining euro zone on convergence of health care expenditure. Panel data set covering 17 cross-sectional units (current eurozone member countries) over 15-years time period is examined using the classical approach to convergence. The analyses presented in this thesis provide evidence of sigma-convergence of HCE as a share of GDP. Conditions for sigma-convergence of HCE per capita are not satisfied. As for beta-convergence, the analysis of HCE as a share of GDP confirm the absolute convergence, conditional convergence did not occur. As for HCE per capita, absolute and conditional convergence hypotheses were affirmed. In both cases of absolute convergence, joining the euro area significantly supported convergence of HCE.
Vedoucí práce: Anna Klosová
Diplomová práce (Ing.)—Vysoká škola ekonomická v Praze. Fakulta mezinárodních vztahů, 2013
Obsahuje bibliografii
Textový (vysokoškolská kvalifikační práce)
Rok obhajoby 2013
Způsob přístupu: Internet
Keywords: diplomové práce; master's theses; economics of globalisation and european integration [obor dipl. práce]